2011
DOI: 10.1111/j.1365-2893.2011.01441.x
|View full text |Cite
|
Sign up to set email alerts
|

HCV genotype 3 is associated with a higher hepatocellular carcinoma incidence in patients with ongoing viral C cirrhosis

Abstract: Liver steatosis is a main histopathological feature of Hepatitis C (HCV) infection because of genotype 3. Steatosis and/or mechanisms underlying steatogenesis can contribute to hepatocarcinogenesis. The aim of this retrospective study was to assess the impact of infection with HCV genotype 3 on hepatocellular carcinoma (HCC) occurrence in patients with ongoing HCV cirrhosis. Three hundred and fifty-three consecutive patients (193 men, mean age 58 ± 13 years), with histologically proven HCV cirrhosis and persis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
123
0
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 162 publications
(128 citation statements)
references
References 29 publications
3
123
0
2
Order By: Relevance
“…However experience from India has shown that genotype 3 is a comparatively difficult genotype to treat [25]. Studies have shown that this genotype is associated with higher steatosis, has a faster progression to fibrosis [26] and has higher incidence of hepatocellular carcinoma [27] along with a poorer treatment response as compared to genotype 2. In an attempt to follow the western guidelines, although it is often presumed that the Indian population would respond in a similar way as Americans or Japanese respond, but it has been shown to be otherwise [25].…”
Section: Implications Of Newer Treatment Modalities -Indian Scenariomentioning
confidence: 99%
“…However experience from India has shown that genotype 3 is a comparatively difficult genotype to treat [25]. Studies have shown that this genotype is associated with higher steatosis, has a faster progression to fibrosis [26] and has higher incidence of hepatocellular carcinoma [27] along with a poorer treatment response as compared to genotype 2. In an attempt to follow the western guidelines, although it is often presumed that the Indian population would respond in a similar way as Americans or Japanese respond, but it has been shown to be otherwise [25].…”
Section: Implications Of Newer Treatment Modalities -Indian Scenariomentioning
confidence: 99%
“…[4] Although HCV G3 was one of those genotypes who achieved a better sustained viral response (SVR) using pegylated interferon and ribavirin (PEG-IFN/Rbv) therapy, [5] the current effectiveness of the new DAAs against HCV G3 leaves a lot to be desired compared with the results obtained with other genotypes [6]. This is a major problem as compared with other genotypes, HCV G3 is associated with faster progression of fibrosis, [7,8] a greater risk for hepatocellular carcinoma (HCC), [8][9][10] and a higher mortality. [11] Why is it so pathogenic and resistant to treatment?…”
Section: Editorialmentioning
confidence: 99%
“…3,24,25) The prevalence of chronic HCV infection continues to rise in many countries, and it is a major cause of cirrhosis and hepatocellular carcinoma. 26,27) HCV-related cirrhosis remains the leading cause of liver transplantation in the US and accounts for nearly 40% of liver transplants in adults.…”
Section: Discussionmentioning
confidence: 99%